Highly Luminescent Organic Nanorods from Air Oxidation of para‐Substituted Anilines for Freestanding Deep‐Red Color Filters. Issue 22 (5th September 2018) - Park, Yoonsang; Park, Cheolwoo; Kim, Joo Sung; Ahn, Tae Kyu; Lim, Ho Sun; Lee, Tae‐Woo; Kwon, Woosung
Abstract: Oxidation of aniline provides useful organic nanostructures with a wide variety of particle morphologies and properties. Accordingly, in the present study, novel luminescent organic nanorods (ONs) are synthesized through one‐step air oxidation of para ‐substituted anilines without any shape‐guiding surfactants. These ONs present highly crystalline rod‐like structures due to the ortho ‐coupling reaction of aniline and π–π interactions between the phenazine‐like structures. Using photoluminescence spectroscopy, absorption spectroscopy, time‐correlated single photon counting, and time‐dependent density functional theory calculation, it is revealed that the phenazine‐like structures in the ONs are largely responsible for their bright, photostable, deep‐red luminescence with absolute quantum efficiency up to 46%. Finally, the potential application of ONs as a freestanding color filter for deep‐red‐light‐emitting devices that could be used for color pixels of future displays is demonstrated. The findings of this study provide a new strategy for the preparation of luminescent organic nanomaterials, and show their potential for optoelectronic applications. Abstract : Novel luminescent organic nanorods (ONs) are synthesized through one‐step air oxidation of para ‐substituted anilines to emit bright, photostable, deep‐red light with absolute quantum efficiency up to 46%, which originates from phenazine‐like structures formed by ortho ‐coupling reaction of anilines. Finally, a freestanding color filter based on ONs for deep‐red‐light‐emitting devices is demonstrated.